Part II: A Qualitative Study of Social Risk Screening Acceptability in Patients and Caregivers - Byhoff, Elena; De Marchis, Emilia H.; Hessler, Danielle; Fichtenberg, Caroline; Adler, Nancy; Cohen, Alicia J.; Doran, Kelly M.; Ettinger de Cuba, Stephanie; Fleegler, Eric W.; Gavin, Nicholas; Huebschmann, Amy G.; Lindau, Stacy Tessler; et al. (American journal of preventive medicine, 2019)
This study aimed to better understand patient and caregiver perspectives on social risk screening across different healthcare settings. As part of a mixed-methods multisite study, the authors conducted semistructured interviews with a subset of adult patients and adult caregivers of pediatric patients who had completed the Center for Medicare and Medicaid Innovation Accountable Health Communities social risk screening tool between July 2018 and February 2019. Interviews, conducted in English or Spanish, asked about reactions to screening, screening acceptability, preferences for administration, prior screening experiences that informed perspectives, and expectations for social assistance. Basic thematic analysis and constant comparative methods were used to code and develop themes. Fifty interviews were conducted across 10 study sites in 9 states, including 6 primary care clinics and 4 emergency departments. There was broad consensus among interviewees across all sites that social risk screening was acceptable. The following 4 main themes emerged: (1) participants believed screening for social risks is important; (2) participants expressed insight into the connections between social risks and overall health; (3) participants emphasized the importance of patient-centered implementation of social risk screening; and (4) participants recognized limits to the healthcare sector's capacity to address or resolve social risks. Despite gaps in the availability of social risk–related interventions in healthcare settings, patient-centered social risk screening, including empathy and attention to privacy, may strengthen relationships between patients and healthcare teams. This article is part of a supplement entitled Identifying and Intervening on Social Needs in Clinical Settings: Evidence and Evidence Gaps, which is sponsored by the Agency for Healthcare Research and Quality of the U.S. Department of Health and Human Services, Kaiser Permanente, and the Robert Wood Johnson Foundation.